Evaluation of different levels of effective microorganism treated teff straw supplementation with concentrate feed on nutrient utilization and performance of yearling local lambs - Abito Asres; Yeshambel Mekuriaw; Likawent Yeheyis (Veterinary Research Notes)
Objective: This investigation aimed to assess various degrees of effective microorganism-treated teff straw supplementation with concentrate feed on nutrient consumption and performance in yearling intact local lambs. Materials and Methods: Twenty-five yearling intact local male lambs weighing an average of 22.55 ± 2.43 kg (mean ± SD) at the beginning of their lives were used in the experiment. For this experiment, a randomized whole-block design was used. Results: According to the results of the study, the CP content of the teff straw treated with different concentrations of beneficial microbes was marginally higher than that of the teff straw that was left untreated. Compared to lambs given untreated teff straw, the growth performance of the sheep in T3, T4, and T5 was considerably (p < 0.001) superior. The mean slaughter bodyweight and hot carcass weight of sheep in T5 were considerably (p < 0.01) greater than those of lambs in untreated teff straw. The partial budget analysis showed that lambs in T3 had a greater marginal rate of return and net income than lambs in other treatments. Conclusion: Local lambs fed 500 ml effective microorganisms per 1 kg treated teff straw with 350 g of concentrate mixture-based feeding resulted in both biologically efficient and economically profitable. [Vet. Res. Notes 2025; 5(1.000): 1-9]